Investigation of thiol‐disulfide homeostasis and ischemia‐modified albumin levels in patients with hidradenitis supurativa. (12th January 2022) - Balik, Zeynep Busra; Balik, Ahmet Rifat; Yucel, Cigdem; Hayran, Yildiz; Çaliskan, Ercan; Erel, Ozcan
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease. The pathogenesis of HS is not clear, and the triggering mechanism for the initiation of the disease is still a controversy. Aims: The present study aims to investigate the relationship between thiol‐disulfide homeostasis (TDH), ischemia‐modified albumin (IMA), and HS. To our knowledge, this will be the first report evaluating TDH and IMA status in HS. Patients/Methods: The study included 30 patients with HS as the patient group and 30 healthy individuals as the control group. For determination of HS severity, Hurley and Hidradenitis suppurativa physician global assessment (PGA) scores were used. One tube venous blood specimen from every participant was obtained. IMA and TDH tests were analyzed in sera of participants. The results were evaluated statistically. Results: Disulfide ( p  < 0.001), Index I ( p  = 0.001), and Index II ( p  = 0.001) levels in HS group were significantly higher than control group. IMA levels in patients with higher Hurley scores are significantly higher ( p  = 0.032, r  = 0.39). A positive correlation was observed between IMA level and disease duration ( p  = 0.021, r  = 0.42). Conclusions: The shift in thiol/disulfide balance toward disulfide and significant increase in IMA levels put out the importance of oxidation status in HS etiopathogenesis.